Detection of Cryptococcus neoformans capsular polysaccharide antigen in asymptomatic HIV-infected patients - Negroni, R.; Cendoya, C.; Arechavala, A.I.; Robles, A.M.; Bianchi, M.; Bava, A.J.; Helou, S. (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
Serum samples from 242 HIV-positive persons were studied for the detection of capsular polysaccha-ride antigen of Cryptococcus neoformans; 193 of these patients presented less than 300 CD4+ cells/µl of blood and 49 patients had more than 300 CD4+ cells/µl. None of them had symptoms or signs characteristic of cryptococcosis. The capsular antigen of C. neofarmans was detected by latex agglutination technique with pronase pre-treatment (IMMY, Crypto-Latex Antigen Detection System, Immunomycologics Inc., OK, USA); in 61% of the samples, ELISA technique was also used (Premier, Cryptococcal Antigen, Meridian Diagnostic Inc., Cincinatti, Oh, USA). The comparative study of both methods showed that the results obtained were similar in 96.9% of the cases. The capsular antigen was detected in 13 out of 193 (6.7%) patients with less than 300 CD4+ cells/µl. Cryptococcosis was confirmed mycologically in 3 of these 13 cases (23%) by the isolation of C. neoformans in CSF or blood cultures. Three patients, who had presented negative results of both tests for capsular antigen, suffered disseminated cryptococcosis 4 to 8 months later. The predictive diagnostic value of capsular antigen detection of C. neoformans seems tobe low and we believe that it should not be done routinely in asymptomatic HIV-positive persons.